EFFECT OF PERSON-ENVIRONMENT FIT ON TURNOVER INTENTION. THE ROLE OF ORGANISATIONAL COMMITEMENT AND ORGANIZATIONAL IDENTIFICATION. - Dr. Pardeep Bawa Sharma (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The purpose of this paper is to examine the effect of Person-Environment fit (PEF) on turnover intention (TIN) through organizational commitement (OCM) and organizational identification (OID) of nurses in multispecialty hospitals in Punjab (Chandigarh and Mohali) province of India. Data were collected from 269 nurses of 4 multispecialty hospitals in early 2020. Structured equation modelling (SEM) was used to test how POF explains TIN through OCM and OID. Results reveal that POF affects TI and OCM and OID mediates between this relationship. Results have multiple implications for hiring teams at these multispecialty hospitals and hospitals in general. Hiring teams must try to access the level of compatibility between the individual and work environment in order to make sure that the chances of that individual as employee go down to a substantial extent to part ways with organization in normal circumstances. The organization as a whole should create a work environment where individuals identify with the organization and are committed towards it. POF in conjunction with OID and OCM can drastically reduce TIN which is an antecedent to actual turnover.